An evaluation of prompting procedures in error correction for children with autism. (14th August 2020) - Yuan, Chengan; Zhu, Jing
Abstract: Error correction is a common instructional strategy for children with autism spectrum disorder (ASD). As prompts are ubiquitous in error correction, we compared the effects of error correction with two prompting procedures (i.e., echoic and picture prompts) for four children with ASD. We used an adapted alternating treatments design embedded in a multiple baseline across participants design. Two comparisons were included to assess whether the relative effects of the arrangements would correspond and replicate within each participant. The results showed that error correction with picture prompt seemed to have produced faster mastery across the two comparisons. Our findings suggest that the various prompting procedure may result in differentiated error‐correction effects. Practitioners may consider assessing the relative effects of error‐correction procedures during treatment selection.